Sarcoidosis-like Skin Lesions as the First Manifestation of Ataxia-Telangiectasia - Borko Milanovic; Gordana Vijatov-Djuric; Andrea Djuretic; Jelena Kesic; Vesna Stojanovic; Milica Jaric; Ognjen Ležakov (Children)
Ataxia-telangiectasia is a rare autosomal recessive disorder that is difficult to diagnose due to its unpredictable presentation. It is characterized by cerebellar degeneration, telangiectasias, immunodeficiency, frequent pulmonary infections, and tumors. Immune system abnormalities manifest as disruptions in both cellular and humoral immunity. The most common findings include decreased levels of immunoglobulin classes (IgA, IgM, IgG, and IgG subclasses) and a reduced number of T and B lymphocytes. A four-year-old girl was initially evaluated and treated for skin lesions that presented as crusts spreading across her body. She was monitored by a pulmonologist due to frequent bronchial obstructions. Over time, she developed bilateral scleral telangiectasia, saccadic eye movements, and impaired convergence. Her gait was wide-based and unstable, with truncal ataxia and a positive Romberg sign. Laboratory tests revealed decreased immunoglobulin G levels, subclass IgG4 levels, elevated alpha-fetoprotein, and a reduced number of T and B lymphocytes. Brain magnetic resonance imaging showed cerebellar atrophy. Whole-exome sequencing identified heterozygous variants c.1564-165del, p.(Glu5221lefsTer43), and c.7630-2A>C in the serine/threonine-protein kinase ATM (ataxia-telangiectasia mutated) gene, confirming the diagnosis of ataxia-telangiectasia. Following diagnosis, treatment with intravenous immunoglobulin replacement was initiated along with infection prevention and management. The goal of this case report is to raise awareness of the atypical initial presentation that may lead to a diagnostic delay. We emphasize the importance of considering ataxia-telangiectasia in the differential diagnosis, even when classical neurological signs are not yet evident.